2008
DOI: 10.1016/j.freeradbiomed.2008.05.026
|View full text |Cite
|
Sign up to set email alerts
|

Reactive oxygen species up-regulate CD11b in microglia via nitric oxide: Implications for neurodegenerative diseases

Abstract: Microglial activation is considered as a hallmark of several neurodegenerative disorders. During microglial activation, the expression of CD11b, the beta-integrin marker of microglia, is increased. However, the molecular mechanism behind increased microglial CD11b expression is poorly understood. The present study was undertaken to explore the role of reactive oxygen species (ROS) in the expression of CD11b in microglial cells. Bacterial lipopolysaccharide (LPS) stimulated the expression of CD11b in mouse BV-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
83
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(84 citation statements)
references
References 50 publications
0
83
0
1
Order By: Relevance
“…Later studies demonstrated that monocytes/macrophages, including microglia, also express NOX, and it is now accepted that NOX activity is found in both phagocytic and non-phagocytic cells, such as astroglia and neurons (49, 251). Therefore, in addition to a role in pathogen defence, NOX participate in multiple cellular processes such as host defence, migration, changes in morphology of microglia, pro-inflammatory gene expression (251), up-regulation of different markers in response to inflammatory stimuli, and microglia-induced neurotoxicity (265). An excellent review on the role of NOX enzymes in the CNS has been recently published (207) and here, we will only provide a brief description of this system.…”
Section: A Nox Systemmentioning
confidence: 99%
“…Later studies demonstrated that monocytes/macrophages, including microglia, also express NOX, and it is now accepted that NOX activity is found in both phagocytic and non-phagocytic cells, such as astroglia and neurons (49, 251). Therefore, in addition to a role in pathogen defence, NOX participate in multiple cellular processes such as host defence, migration, changes in morphology of microglia, pro-inflammatory gene expression (251), up-regulation of different markers in response to inflammatory stimuli, and microglia-induced neurotoxicity (265). An excellent review on the role of NOX enzymes in the CNS has been recently published (207) and here, we will only provide a brief description of this system.…”
Section: A Nox Systemmentioning
confidence: 99%
“…The factors which trigger the age-related activation of glia are not known, although a change in the balance between pro-and anti-inflammatory cytokines, as well as dysregulation of antioxidative processes, which are likely to promote activation, have been reported (Nolan et al, 2005;Roy et al, 2008). In addition, glial cell activation by infiltrating peripheral cells has been reported recently (McQuillan et al, 2010;Murphy et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…38 Conversely, others indicated that ROS was a key player in microglial activation in which ROS increased microglial expression of CD11b via NO. 39 In fact, a recent study showed that activation of CD11b via inside-out signaling negatively regulated TLRtriggered proin°ammatory response. 40 Taken together, the current investigation demonstrates that LPLI can enhance microglial phagocytic activity through activation of PI3K/Akt pathway in LPS-induced neuroin°ammation model.…”
Section: Discussionmentioning
confidence: 99%